Penerapan Manajemen Stres untuk Menurunkan Tingkat Kecemasan Remaja di SMPN 40 Semarang - Tuti Anggarawati; Akmilia Vika Ananda Putri (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Adolescence is a transition period from childhood to adulthood, from the beginning of puberty until maturity is reached. Anxiety arises from emotional states that arise when individuals are stressed. The cause of anxiety is stress, so stress management is needed to control or regulate stress so that anxiety does not trigger the emergence of mental disorders.Accompanied by symptoms of pressure, confusion, fear and external threats. Stress management can anticipate, prevent, manage and recover from stress felt due to threats and inability to cope. The aim of the case study is to provide an overview of the application of stress management to reduce adolescent anxiety levels. The method used descriptive research with a case study approach method. The instrument used the Hamilton Rating Scale For Anxiety (HRS-A) questionnaire sheet. The results showed that the level of anxiety before implementing was 33 for subject I and 30 for subject II in the severe anxiety level category. After implementing the case study, it was found that the level of anxiety decreased, subject I by 15 and subject II by 14 in the mild anxiety category. This research concludes that stress management can reduce anxiety levels in adolescents.